What is the optimal dwell time for maximizing ultrafiltration with icodextrin exchange in automated peritoneal dialysis patients? - (:unkn) unknown (Multimed Inc., 2006)
◆ Background: Icodextrin is increasingly being used in automated peritoneal dialysis (APD) for the long dwell exchange to maintain adequate ultrafiltration (UF). However, the UF reported in the literature varies with different dwell times: from 200 to 500 mL with 12 - 15 hour dwells. In order to maximize UF, it is important to know the relationship between dwell time and UF when using icodextrin in APD patients. With this knowledge, decisions can be made with respect to dwell period, and adjustments to the dialysis prescription can be made accordingly. ◆ Methods: We prospectively studied this relationship in 36 patients from Canada and Turkey. All patients did the icodextrin day exchange manually after disconnecting themselves from overnight cycler dialysis. Dwell period was increased by 1 hour every week, from 10 to 14 hours. Ultra-filtration was noted for each icodextrin exchange. Mean UF for each week (i.e., dwell period) was compared by repeated measures ANOVA. ◆ Results: We found no difference in mean UF with increasing dwell time: 351.73 ± 250.59 mL at 10 hours versus 371.75 ± 258.25 mL at 14 hours (p = 0.83). We also compared mean UF between different subgroups and found that males (p = 0.02 vs females) and high transporters (p = 0.04 vs low) had higher mean UF. Further analysis of maximal UF showed no correlation to age, sex, diabetic status, transport category, creatinine clearance, Kt/V, duration on peritoneal dialysis, or duration of icodextrin use. ◆ Conclusion: Icodextrin-related UF in APD patients is not related to demographic factors and does not increase significantly beyond 10 hours. © 2006 International Society for Peritoneal Dialysis.
Keywords: Automated peritoneal dialysis; Icodextrin; Ultrafiltration